Using patients' experiences to identify priorities for quality improvement in breast cancer care: patient narratives, surveys or both? - Tsianakas Vicki; Maben Jill; Wiseman Theresa; Robert Glenn; Richardson Alison; Madden Peter; Griffin Mairead; Davies Elizabeth A (BMC, 2012)
Abstract Background Patients' experiences have become central to assessing the performance of healthcare systems worldwide and are increasingly being used to inform quality improvement processes. This paper explores the relative value of surveys and detailed patient narratives in identifying priorities for improving breast cancer services as part of a quality improvement process. Methods One dataset was collected using a narrative interview approach, (n = 13) and the other using a postal survey (n = 82). Datasets were analyzed separately and then compared to determine whether similar priorities for improving patient experiences were identified. Results There were both similarities and differences in the improvement priorities arising from each approach. Day surgery was specifically identified as a priority in the narrative dataset but included in the survey recommendations only as part of a broader priority around improving inpatient experience. Both datasets identified appointment systems, patients spending enough time with staff, information about treatment and side effects and more information at the end of treatment as priorities. The specific priorities identified by the narrative interviews commonly related to 'relational' aspects of patient experience. Those identified by the survey typically related to more 'functional' aspects and were not always sufficiently detailed to identify specific improvement actions. Conclusions Our analysis suggests that whilst local survey data may act as a screening tool to identify potential problems within the breast cancer service, they do not always provide sufficient detail of what to do to improve that service. These findings may have wider applicability in other services. We recommend using an initial preliminary survey, with better use of survey open comments, followed by an in-depth qualitative analysis to help deliver improvements to relational and functional aspects of patient experience.